Stress inducible proteinase inhibitor diversity in capsicum annuum - Mishra, Manasi; Mahajan, Neha S.; Tamhane, Vaijayanti A.; Kulkarni, Mahesh J.; Baldwin, Ian T.; Gupta, Vidya S.; Giri, Ashok P. (BMC Plant Biology, 2012)
Background: Wound-inducible Pin-II Proteinase inhibitors (PIs) are one of the important plant serine PIs which have been studied extensively for their structural and functional diversity and relevance in plant defense against insect pests. To explore the functional specialization of an array of Capsicum annuum (L.) proteinase inhibitor (CanPIs) genes, we studied their expression, processing and tissue-specific distribution under steady-state and induced conditions. Inductions were performed by subjecting C. annuum leaves to various treatments, namely aphid infestation or mechanical wounding followed by treatment with either oral secretion (OS) of Helicoverpa armigera or water. Results: The elicitation treatments regulated the accumulation of CanPIs corresponding to 4-, 3-, and 2-inhibitory repeat domains (IRDs). Fourty seven different CanPI genes composed of 28 unique IRDs were identified in total along with those reported earlier. The CanPI gene pool either from uninduced or induced leaves was dominated by 3-IRD PIs and trypsin inhibitory domains. Also a major contribution by 4-IRD CanPI genes possessing trypsin and chymotrypsin inhibitor domains was specifically revealed in wounded leaves treated with OS. Wounding displayed the highest number of unique CanPIs while wounding with OS treatment resulted in the high accumulation of specifically CanPI-4, -7 and -10. Characterization of the PI protein activity through two dimensional gel electrophoresis revealed tissue and induction specific patterns. Consistent with transcript abundance, wound plus OS or water treated C. annuum leaves exhibited significantly higher PI activity and isoform diversity contributed by 3- and 4-IRD CanPIs. CanPI accumulation and activity was weakly elicited by aphid infestation yet resulted in the higher expression of CanPI-26, -41 and -43. Conclusions: Plants can differentially perceive various kinds of insect attacks and respond appropriately through activating plant defenses including regulation of PIs at transcriptional and post-translational levels. Based on the differentially elicited CanPI accumulation patterns, it is intriguing to speculate that generating sequence diversity in the form of multi-IRD PIs is a part of elaborative plant defense strategy to obtain a diverse pool of functional units to confine insect attack.
Keywords: CanPI; Herbivory; Oral secretions; Pin-II type proteinase inhibitors; Plant-insect interaction

Stress inducible proteomic changes in capsicum annuum leaves - Mahajan, Neha S.; Mishra, Manasi; Tamhane, Vaijayanti A.; Gupta, Vidya S.; Giri, Ashok P. (Plant Physiology and Biochemistry, 2014)
Herbivore attack induces defense responses in plants, activating several signaling cascades. As a result, molecules deterrent to the herbivores are produced and accumulated in plants. Expression of defense mechanism/traits requires reorganization of the plant metabolism, redirecting the resources otherwise meant for growth. In the present work, protein profile of Capsicum annuum leaves was examined after herbivore attack/induction. Majority of proteins identified as differentially accumulated, were having roles in redox metabolism and photosynthesis. For example, superoxide dismutase and NADP oxidoreductase were upregulated by 10- and 6-fold while carbonic anhydrase and fructose-1,6-bisphosphatase were downregulated by 9- and 4-fold, respectively. Also, superoxide dismutase, NADPH quinone oxidoreductase and NADP dependent isocitrate dehydrogenase transcripts showed a higher accumulation in induced leaf tissues at early time points. In general, proteins having role in defense and damage repair were upregulated while those involved in photosynthesis appeared downregulated. Thus metabolic reconfiguration to balance defense and tolerance was evident in the stress-induced leaves. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Capsicum annuum; Oxidative stress; Wounding

Structural features of diverse Pin-II proteinase inhibitor genes from capsicum annuum - Mahajan, Neha S.; Dewangan, Veena; Lomate, Purushottam R.; Joshi, Rakesh S.; Mishra, Manasi; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
The proteinase inhibitor (PI) genes from Capsicum annuum were characterized with respect to their UTR, introns and promoter elements. The occurrence of PIs with circularly permuted domain organization was evident. Several potato inhibitor II (Pin-II) type proteinase inhibitor (PI) genes have been analyzed from Capsicum annuum (L.) with respect to their differential expression during plant defense response. However, complete gene characterization of any of these C. annuum PIs (CanPIs) has not been carried out so far. Complete gene architectures of a previously identified CanPI-7 (Beads-on-string, Type A) and a member of newly isolated Bracelet type B, CanPI-69 are reported in this study. The 5' UTR (untranslated region), 3'UTR, and intronic sequences of both the CanPI genes were obtained. The genomic sequence of CanPI-7 exhibited, exon 1 (49 base pair, bp) and exon 2 (740 bp) interrupted by a 294-bp long type I intron. We noted the occurrence of three multi-domain PIs (CanPI-69, 70, 71) with circularly permuted domain organization. CanPI-69 was found to possess exon 1 (49 bp), exon 2 (551 bp) and a 584-bp long type I intron. The upstream sequence analysis of CanPI-7 and CanPI-69 predicted various transcription factor-binding sites including TATA and CAAT boxes, hormone-responsive elements (ABRELATERD1, DOFCOREZM, ERELEE4), and a defense-responsive element (WRKY71OS). Binding of transcription factors such as zinc finger motif MADS-box and MYB to the promoter regions was confirmed using electrophoretic mobility shift assay followed by mass spectrometric identification. The 3' UTR analysis for 25 CanPI genes revealed unique/distinct 3' UTR sequence for each gene. Structures of three domain CanPIs of type A and B were predicted and further analyzed for their attributes. This investigation of CanPI gene architecture will enable the better understanding of the genetic elements present in CanPIs.
Keywords: CanPI; Capsicum; Gene architecture; Promoter; Proteinase inhibitor